Dead until dark - Harris, Charlaine (New York : Ace Books, 2008)
Love blossoms between Sookie Stackhouse, a cocktail waitress who keeps to herself because of her ability to read minds, and Bill, a vampire with ties to a crowd that may be responsible for the death of one of Sookie's coworkers.
Reprint. Originally published: 2001
'Now the HBO original series True Blood'--Cover